Open-path dual-frequency comb spectroscopy of methane from livestock production - Morris, Lindsay (Kansas State University, 2023)
This project focuses on providing outdoor open-path spectroscopic measurements for detection of methane and other agriculturally significant gases over long periods of time in an agricultural setting. The use of dual-comb spectroscopy for remote sensing on agricultural sites has led to an aptly named system, the Agrocombs. The decomposition and fermentation of food performed by microbes in the stomach of ruminants, known as enteric fermentation, is one of the largest sources of anthropogenic methane emissions in the US due in large part by the dense population of livestock such as cattle. Several long-range open-path remote sensing techniques, such as Fourier transform infrared spectroscopy or tunable laser absorption spectroscopy, could be considered to detect and identify methane in an agricultural setting, but limitations in these techniques prove to be deterrents in their applications. Dual-comb spectroscopy provides a unique advantage of simultaneously measuring several significant gases (such as CH₄, NH₃, CO₂, and H₂O) with no external reference system or large structural support. Applying this method to agricultural processes began the journey of the Agrocombs system, a dual-comb pulsed laser system designed to be mobile and noninvasive enough to be placed on a site without disruption of operations, while performing long-term measurements of significant agricultural gases to result in concentration data. To prove the merit of this system, the Agrocombs research group performed a 2019 measurement at a KSU operated beef stocker site in parallel to a closed-path cavity ring-down system commonly used for trace gas measurements. The results of this experiment show an agreement between the two systems of 6% for methane, with the Agrocombs system providing a concentration precision of 1.25 ppm·m at 900 s. Additionally, the Agrocombs system was able to record concentrations for carbon dioxide, ammonia, and water vapor simultaneously without additional equipment. After a successful measurement in a feedlot system, where the cattle are confined in pens and present in large numbers, the next step has been to move towards a pasture to capture measurements of cattle in another important lifestyle, grazing. Grazing cattle in a pasture system provide a unique measurement potential for the Agrocombs system due to the low animal density and the presence of methane sinks that can detract from overall methane production and discharge, otherwise known as emissions. Traditional models for cattle emissions tend to lean towards the assumption that cattle contribute uniformly based on number of cattle in a system, but often neglect the complexity of a system’s additional factors to the gas cycle. Pastures provide more area for less animals, allowing for free roaming and independent grazing, which differs greatly from our previous measurement. Additionally, microbial activity in the soil may prove to act as a methane sink in native grasslands, reducing the overall contributions of the grazing system. While feedlot emissions were found to be approximately 137±86 µg/m²/s, we expect that the contributing factors of less cattle in a larger area of interest, combined with the methane sink of microbial activity in the soil, will garner us a net methane emission in a pasture of an order of magnitude less than the feedlot. In order to measure emissions from a pasture, the Agrocombs project must achieve a precision of approximately 0.2 parts per billion (ppb), significantly smaller than the approximate 3 ppb in our feedlot measurement, determined through simulation. To test our precision and work towards this goal, we will conduct a controlled release experiment to mimic cattle in a pasture. This also allows for testing a newly packaged system and its accompanying equipment, as well as techniques to handle the ever-moving cattle and their large area of mobility. This thesis details the beginnings and preliminary results of a controlled release in a pasture, as well as the steps taken to achieve such precision needed for this difficult sensing measurement.
Keywords: Dual comb spectroscopy; Micrometeorology; Agricultural sensing; Ultrafast laser